The relationship between an inflammation-based prognostic score (Glasgow Prognostic Score) and changes in serum biochemical variables in patients with advanced lung and gastrointestinal cancer. Issue 6 (27th April 2006) - Brown, D J F; Milroy, R; Preston, T; McMillan, D C
Abstract : Background: The Glasgow Prognostic Score (GPS), an inflammation-based prognostic score formed from standard thresholds of C reactive protein (CRP) and albumin, has prognostic value in patients with advanced cancer. Little is known about the general biochemical disturbance associated with the systemic inflammatory response in cancer. Aim: To examine the relationship between the GPS and blood biochemistry in patients with advanced lung and gastrointestinal cancer. Methods: The GPS (albumin <35 g/l = 1 and CRP >10 mg/l = 1 combined to form a prognostic score of 0 (normal) and 1 or 2 (abnormal)) and a variety of biochemical variables were examined in patients (n = 50) with advanced lung or gastrointestinal cancer and in a healthy control group (n = 13). Results: The GPS was normal in all the controls, but abnormal in 78% of the cancer group. Serum levels of sodium, chloride, creatine kinase, zinc and vitamin D were lower in the cancer group (all p<0.01), whereas levels of calcium, copper (both p<0.05), alkaline phosphatase, γ-glutamyl transferase (both p<0.001) and lactate dehydrogenase (p<0.10) were raised. In the patient group, with increasing GPS, there was a median reduction in Karnofsky Performance Status (25%), haemoglobin (22%), sodium (3%), zinc (15%) and survival (93%, all p<0.05) and a median increase in white cell count (129%), alkaline phosphatase (217%), γ-glutamyl transferase (371%) and lactate dehydrogenase (130%, all p<0.05). CRP levels were strongly and similarly correlated with alkaline phosphatase and γ-glutamyl transferase, accounting for more than 25% of the variation in their activities. Conclusion: Several correlations were seen between biochemical variables and increasing GPS. In particular, chronic activation of the systemic inflammatory response in cancer was associated with increase in γ-glutamyl transferase and alkaline phosphatase activity in patients with advanced lung and gastrointestinal cancer.